Complete Mitogenome and Phylogenetic Analysis of a Marine Ray-Finned Fish, Alcichthys elongatus (Perciformes: Cottidae) - Maheshkumar Prakash Patil; Jong-Oh Kim; Seung Hyun Yoo; Yong Bae Seo; Yu-Jin Lee; Jin-Koo Kim; Shin-Ichi Kitamura; Gun-Do Kim (Fishes, 2023)
Alcichthys elongatus is the only species in the genus, and this work is the first to provide a comprehensive mitogenome analysis of this species. The A. elongatus mitogenome was 16,712 bp long, with biased A + T content (52.33%), and featured thirteen protein-coding genes (PCGs), twenty-two tRNAs, two rRNAs, and the control region (D-loop). The H strand encoded twenty-eight genes (twelve PCGs, fourteen tRNA, and two rRNA) and the control region, whereas the L strand encoded the remaining nine genes (ND6 and eight tRNA). Except for COXI, which started with GTG, all PCG sequences started with ATG and ended with TAA (ND4L, ND5, COXI, ATP8) or TAG (ND1, ND6) termination codons, with some (ND2, ND3, ND4, COXII, COXIII, ATP6, Cytb) having an incomplete termination codon. Except for tRNA-serine-1 (trnS), the majority of the tRNAs exhibited characteristic cloverleaf secondary structures. Based on 13 PCGs, phylogenetic analysis placed A. elongatus in the same clade as Icelus spatula. This genomic data will be useful for species identification, phylogenetic analysis, and population genetics.